3PC-035 So, happy? automated nominative dispensation: satisfaction survey of the nursing staff - Taton, A (Eur J Hosp Pharm, 2018)
BACKGROUND: Within the framework of the order of 27 April 2017 concerning the standard contract of improvement in the quality and the efficiency of care (CAQES), securing patients’ medicinal care is a priority. The automation of the individual nominative daily dispensing (DDIN) is a means of securing the dispensation. Since August 2013, an automated dispensing system with surconditionnement of the dry oral forms is implemented in the pharmacy: ACCED 220(®) of the Eco-Dex company. Its implementation has required many organisational choices within the pharmacy and of the care services. PURPOSE: The objective is to evaluate the degree of satisfaction of the nursing staff and their sense of security with the automated DDIN. MATERIAL AND METHODS: An anonymous satisfaction questionnaire was distributed in 13 care services. RESULTS: Eighty questionnaires were returned to the pharmacy: 45% of respondents experienced changes in practice following the automation of the DDIN. Overall, 84% of the nurses expressed a sense of safety with the automated DDIN in the stages of drug management, of which 85% for the verification of prescriptions, 87% for the preparation of pillboxes and 80% for the administration of treatments. The main criteria perceived as improved with the automation of the DDIN are in descending order: drug identification (90%), identititovigilance (78%), reduction of preparation errors (62%) and the conformity of pillboxes with regard to the prescription (61%). Concerning the realisation of certain stages of drug management, the automation of the DDIN allowed a moderate time saving in the preparation of drug distribution (63%), although time spent on orders, drug distribution and administration remained unchanged (56%, 72% and 88%, respectively of nurses interviewed) compared to the manual DDIN. The overall satisfaction rate of the automated DDIN is 90% (72% rather satisfied and 18% very satisfied). CONCLUSION: Through this questionnaire, we confirm the degree of satisfaction and feeling of safety expected from the nursing staff. The automatic dispensing system ensures safe drug dispensing, but potential errors can possibly be generated because of lack of control due to excessive confidence in the system. It is therefore necessary to put in place a risk-management approach related to this activity. No conflict of interest